Development and characterization of micelles for nucleolin-targeted co-delivery of docetaxel and upconversion nanoparticles for theranostic applications in brain cancer therapy - Chauhan M.; Singh R.P.; Sonali; Yadav B.; Shekhar S.; Kumar A.; Mehata A.K.; Nayak A.K.; Dutt R.; Garg V.; Kailashiya V.; Muthu M.S.; Koch B.; Pandey D.K. (My University, 2025)
Despite the existence of several treatment modalities and advancements in cancer research, brain cancer is still incurable. Over-expression of nucleolin receptors on cancer cells has been explored in several studies. The study aimed to develop and characterize nucleolar -targeted theranostic pluronic F127-TPGS micelles for brain cancer therapy. The theranostic agents i.e., Docetaxel; DTX as a therapeutic agent, and the upconversion nanoparticles; UCNP as a diagnostic agent, were loaded into micelles by a slightly-modified solvent casting method. Micelles were further decorated with synthesized TPGS-AS1411 aptamer conjugate for targeting brain cancer cells. The prepared micelles were found between 90 and 165 nm, with a uniform homogeneous and narrow distribution in formulations. DTX and UCNP encapsulation efficiencies of micelles were found 74–88% and 38–40%, respectively. Micelles have depicted sustained release of DTX for as long as 72 h. Hemolytic assay confirmed that DUTP-AS1411 aptamer micelles were found more biocompatible than Taxotere®. The cytotoxicity results revealed that DTP, DUTP, and DUTP-AS1411 aptamer micelles achieved 4.20, 11.70, and 17.54-fold more effectiveness than Taxotere®, after 24 h of therapy, respectively. In addition, DUTP-AS1411 aptamer micelles achieved higher tmax and Cmax of DTX up to 8- and 1.5-fold, respectively, compared to Taxotere® treated group. A similar trend was observed for the brain-distribution study as DUTP-AS1411 aptamer micelles were found more efficacious than Taxotere®. The histopathology studies showed no toxicity and cellular damage even after the 14th and 28th day post i.v. administration of normal saline, DTP, DUTP, and DUTP-AS1411 aptamer micelles formulations whereas Taxotere® has reported to cause toxicity in brain tissues. The study revealed that DUTP-AS1411 aptamer micelles inherit promising and improved therapeutic efficacy, reduced toxicity, dosing frequency, and sustained drug release behavior which can be further exploited as a potential therapeutic approach for brain cancer. © 2023 Elsevier B.V.